Corrosion Behavior of Tempered Dual-Phase Steel Embedded in Concrete - Keleştemur, Oğuzhan; Aksoy, Mustafa; Yıldız, Servet (My University, 2009)
Dual-phase (DP) steels with different martensite contents were obtained by appropriate heat treatment of an SAE1010 structural carbon steel, which was cheap and widely used in the construction industry. The corrosion behavior of DP steels in concrete was investigated under various tempering conditions. Intercritical annealing heat treatment was applied to the reinforcing steel to obtain DP steels with different contents of martensite. These DP steels were tempered at 200, 300, and 400°C for 45 min and then cooled to room temperature. Corrosion experiments were conducted in two stages. In the first stage, the corrosion potential of DP steels embedded in concrete was measured every day for a period of 30 d based on the ASTM C 876 standard. In the second stage, the anodic and cathodic polarization values of these steels were obtained and subsequently the corrosion currents were determined with the aid of cathodic polarization curves. It was observed that the amount of second phase had a definite effect on the corrosion behavior of the DP steel embedded in concrete. As a result of this study, it is found that the corrosion rate of the DP steel increases with an increase in the amount of martensite.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Dual-phase steel; Corrosion; Tempering treatment; Martensite; Concrete